Bhagata Jallhaṇa (Vārisa S̱āha Fāuṇḍes̱ana, 2009)
Poems of Jaḷḷana, 1586-1644, Panjabi saint poet; includes his life introduction in brief
Poems. - Includes bibliographical references. - Panjabi in Gurmukhi-Schr
Keywords: Jaḷḷana 1586-1644; Panjabi poetry